Implementasi Program Bimbingan Karir Dalam Upaya Peningkatan Studi Lanjut Siswa di SMA Negeri 1 Purwodadi Kabupaten Grobogan - Sri Wahyuni; Bunyamin Bunyamin; Muhammad Prayito (Jayapangus Press, 2026)
This study aims to analyze the implementation of a career guidance program in supporting students’ continuing education at SMA Negeri 1 Purwodadi, Grobogan Regency. The study focuses on four managerial functions: planning, organizing, implementation, and evaluation of the career guidance program. A qualitative case study approach was employed, involving the principal, counseling coordinator, counseling teachers, homeroom teachers, and students as research participants. Data were collected through interviews, observations, and document analysis and were analyzed using the Miles and Huberman interactive model. The findings indicate that program planning was conducted through students’ needs assessment, mapping of educational interests, and preparation of annual guidance services. Program organization involved clear task distribution among school personnel and collaboration with alumni and higher education institutions. Program implementation was carried out through career information services, educational fairs, campus visits, alumni sharing sessions, career counseling, socialization of university admission pathways, and assistance with university applications. Program evaluation was conducted through monitoring, outcome assessment, and follow-up improvements. The study concludes that the career guidance program has been implemented systematically and collaboratively, contributing to students’ motivation, readiness, and understanding of opportunities for continuing education.